Analysis on the Employability Skills of UNITEN Graduates in Engineering Program - Fadhilah A.R. (Institute of Electrical and Electronics Engineers Inc., 2023)
Communication; Engineering education; Human resource management; Problem solving; Regression analysis; Cumulative grade point averages; Employability; Engineering graduates; Entrepreneurial skills; Leadership; Performance; Problem solving skills; Professionalism; Students